Nicotine associates to intracellular Mycobacterium tuberculosis inducing genes related with resistance to antimicrobial peptides. (26th November 2021) - de Haro-Acosta, Jeny; Jacobo-Delgado, Yolanda M.; Rodríguez-Carlos, Adrian; Torres-Juárez, Flor; Araujo, Zaida; Serrano, Carmen J; Gonzalez-Curiel, Irma; Hernández-Pando, Rogelio; Salinas, Eva; Rivas-Santiago, Bruno
Abstract: Tobacco consumption is related to an increased risk to develop tuberculosis. Antimicrobial peptides are essential molecules in the response to Mycobacterium tuberculosis ( Mtb ) because of their direct antimicrobial activity. The aim of this study was to demonstrate that nicotine enters into Mtb infected epithelial cells and associates with the mycobacteria inducing genes related to antimicrobial peptides resistance. Epithelial cells were infected with virulent Mtb, afterwards cells were stimulated with nicotine. The internalization of nicotine was followed using electron and confocal microscopy. The lysX expression was evaluated isolating mycobacterial RNA and submitted to RT-PCR analysis. Our results indicated that nicotine promotes Mtb growth in a dose-dependent manner in infected cells. We also reported that nicotine induces lysX expression. In conclusion, nicotine associates to intracellular mycobacteria promoting intracellular survival.